CONCEPTUAL APPROACHES TO REGULATING THE INTERACTION BETWEEN KEY PARTICIPANTS OF THE NATIONAL PAYMENT SYSTEM - Elena V. Altukhova (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
By analyzing the present situation the author puts forward the key directions of developing the national payment system which can provide efficiency and stability of its elements. The article deals with the most important issues of security of the national payment system functioning that require urgent solution, principle sources of risks are also identified. Specific features of settlement and payment relations were shown. The necessity to use innovation tools for regulation and to accompany deals for the development of payment relations was demonstrated and it imposes certain restrictions on realization of standard methods of system regulation. The author formulated the conceptual approaches fostering efficient interaction of the key participants of the payment system.